2014
DOI: 10.4312/elope.11.1.113-136
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Literature in EFL Textbooks – A Quest for Camelot?

Abstract: SummaryThe article sets out to explore the proven benefits of using literature in EFL, which have been established in recent (theoretical) sources, including methodology books for teachers. It then moves on to examine the presence of literary texts in a selection of past and current EFL course books spanning over a period of almost seven decades. The results reveal that literature, while mostly perceived as beneficial, is not widely used in the EFL arena today. Finally, some possible reasons for the decline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…While enlightening, many of these studies adopt a completely descriptive approach to discussing textbooks that is short on details, for example, the number of literary texts included in each textbook, text type, genre, and readability. Skela’s (2014) study, in this respect, is one of the few studies to take a more systematic, empirical approach to analysing textbook literary content. Investigating seven EFL textbooks (old and new) used in Slovenian secondary schools for text type, accompanying activities, genre, and text age, Skela reports that the more modern textbooks in his study contain less literary content than older textbooks, favour prose over poetry, with plays being the least represented, and do not have a systematic approach to incorporating literature.…”
Section: The Language Textbook and The Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…While enlightening, many of these studies adopt a completely descriptive approach to discussing textbooks that is short on details, for example, the number of literary texts included in each textbook, text type, genre, and readability. Skela’s (2014) study, in this respect, is one of the few studies to take a more systematic, empirical approach to analysing textbook literary content. Investigating seven EFL textbooks (old and new) used in Slovenian secondary schools for text type, accompanying activities, genre, and text age, Skela reports that the more modern textbooks in his study contain less literary content than older textbooks, favour prose over poetry, with plays being the least represented, and do not have a systematic approach to incorporating literature.…”
Section: The Language Textbook and The Curriculummentioning
confidence: 99%
“…Learners, too, consider literature to be an effective learning tool so long as it focuses on developing their language skills (Bloemert, Paran, Jansen, & van de Grift, 2019) and consists of prose rather than poetry (Akyel & Yalçin, 1990). Studies on textbook literary content, when compared to the amount of research on teacher and student beliefs about literature, have been far fewer in number (Skela, 2014; Takahashi, 2015), with most authors focusing on literature beyond the textbook (see Paran, 2008) and almost exclusively on English. Other times, studies have delved into themes like the representation of ethnicities, race, gender, and political ideologies in textbooks (Bori, 2018), which, while they can play a role in developing literature for language textbooks, are often hidden (Hilliard, 2014) and might not be readily apparent to or even understood by teachers or students.…”
Section: Introductionmentioning
confidence: 99%
“…One of the existing strands taps into the positive effects of using creative poetry writing as a means of approaching EFL (Hanauer, 2010(Hanauer, , 2012(Hanauer, , 2015. The extent to which literature is present in EFL textbooks has also been examined with conclusions which highlight a decrease in the use of literature-based activities in textbooks throughout the 21st century (Skela, 2014). Studies focusing on teachers have documented anecdotal use of literature in FL lessons (Gilroy, 1995).…”
Section: The Use Of Literature In Efl: State Of the Art And Main Chalmentioning
confidence: 99%
“…These textbooks, edited by Russian language experts with occasional input from native speakers, have regularly been criticized for containing inauthentic language and substandard content (Lovtsevich, 2016;Pitina, 2015;Ter-Minasova, 2005), although studies that have included actual teacher feedback or an empirical analysis of the literary content in textbooks appear to be absent in the Russian context. Internationally, studies indicate that the amount of literary content found in contemporary EFL textbooks can be quite limited and has actually been steadily decreasing over time (Gümüşok, 2013;Skela, 2014;Takahashi, 2015;Yildirim, 2012). Gümüşok (2013), for example, discovered that while the EFL textbooks used at Turkish universities had a considerable amount of reading content, the number of literary texts was very limited, with more recently published textbooks containing less literary content than older textbooks.…”
Section: Text Selection and Textbook Qualitymentioning
confidence: 99%